Transdiaphragmatic rupture of hydatid cyst: A rare case report - Kumar, Naveen; -, Shubham; Garg, Ravinder; Khutan, Himanshu; Chahal, Jasmeen (Indian Journal of Case Reports, 2024)
Hydatid disease is a major zoonotic disease worldwide. It remains a serious health problem in developing countries and in countries where animal husbandry is common. Here, we report the case of a 40-year-old male who presented with chief complaints of pain in the right upper quadrant of the abdomen and swelling of the right side lower chest for 2 days. He mentioned intermittent episodes of pain within the past 7 days, the frequency and severity of which is increasing in the past 2 days. Chest X-ray suggestive of opacity of the right lower hemithorax with blunting of cardiophrenic angle seems like pleural effusion with opacity in the right upper lobe but on ultrasound, cystic area with multiple septations found in right lung parenchyma likely suggestive of hydatid cyst.